2006
DOI: 10.1128/mcb.26.7.2595-2614.2006
|View full text |Cite
|
Sign up to set email alerts
|

Rab22a Regulates the Sorting of Transferrin to Recycling Endosomes

Abstract: Rab22a is a member of the Rab family of small GTPases that localizes in the endocytic pathway. In CHO cells, expression of canine Rab22a (cRab22a) causes a dramatic enlargement of early endocytic compartments. We wondered whether transferrin recycling is altered in these cells. Expression of the wild-type protein and a GTP hydrolysis-deficient mutant led to the redistribution of transferrin receptor to large cRab22a-positive structures in the periphery of the cell and to a significant decrease in the plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 32 publications
(51 reference statements)
7
91
0
Order By: Relevance
“…It is also possible that subcellular localization or other unidentified mechanisms might sharpen the specificity for RAB5 and/or RAB21, or otherwise provide conditions favorable for activation of RAB22. Recent studies indicate that RAB5, RAB21 and RAB22 have overlapping subcellular distributions in the endosomal system and may have distinct functional roles in common or related endocytic processes [28][29][30][31][32]46 . One hypothesis consistent with the structural observations, specificity profiles and currently available cell-biological data is that RABEX-5, RIN1 and potentially other mammalian VPS9 domain GEFs have coevolved with RAB5-subfamily GTPases from common progenitors in lower ancestral eukaryotes to facilitate and coordinate more elaborate control mechanisms required for regulation of complex endosomal trafficking networks in higher eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that subcellular localization or other unidentified mechanisms might sharpen the specificity for RAB5 and/or RAB21, or otherwise provide conditions favorable for activation of RAB22. Recent studies indicate that RAB5, RAB21 and RAB22 have overlapping subcellular distributions in the endosomal system and may have distinct functional roles in common or related endocytic processes [28][29][30][31][32]46 . One hypothesis consistent with the structural observations, specificity profiles and currently available cell-biological data is that RABEX-5, RIN1 and potentially other mammalian VPS9 domain GEFs have coevolved with RAB5-subfamily GTPases from common progenitors in lower ancestral eukaryotes to facilitate and coordinate more elaborate control mechanisms required for regulation of complex endosomal trafficking networks in higher eukaryotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…A previously described shRNA specific for human Rab22 (Magadan et al, 2006) was used in this study and expressed in HeLa cells via the pSIREN-RetroQ-DsRed-Express vector, which simultaneously expressed dsRed-Express, an RFP, for identification of transfected cells by fluorescence microscopy. The effective knock down of Rab22 expression in the cell was confirmed by immunofluorescence microscopy with an anti-Rab22 antibody.…”
Section: Inhibition Of Rab22 Via Shrna Blocks Membranementioning
confidence: 99%
“…Rab22 is another Rab GTPase localized on early endosomes and is closely related to Rab5 with 52% sequence identity (Olkkonen et al, 1993;Kauppi et al, 2002). Inhibition of Rab22 function via small interfering RNA (siRNA) blocks recycling of endocytosed cargoes such as transferrin receptor and MHC-I (Weigert et al, 2004;Magadan et al, 2006). Overexpression of Rab22 in the cell leads to enlargement of early endosomes (Kauppi et al, 2002), similar to the effect of Rab5.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the transport back to the trans-Golgi-network might be hindered in L7En-2 PCs since expression of genes involved in these processes, gga2 and rab21 (Black and Pelham, 2000;Simpson et al, 2004) were found to be reduced following En-2 overexpression. Finally, genes involved in recycling of endocytic vesicles (rab22a, snx10 and snx15; Magadan et al, 2006;Qin et al, 2006;Phillips et al, 2001) were also reduced in expression. Taken together, the set of differentially expressed genes following En-2 overexpression pinpoint to a dysregulation of vesicle formation, maturation and sorting; such interpretation is fully consistent with the morphologically observed changes in L7En-2 PCs, from the conspicuous absence of the Golgi apparatus from the axonal pole, to the delayed and reduced dendritogenesis in these cells (Jankowski et al, 2004).…”
Section: Intracellular Transport and Sorting Of Vesicles Are Targetedmentioning
confidence: 99%